Primary hepatic methotrexate-associated lymphoproliferative disorder associated with Epstein-Barr virus reactivation and accompanied by spontaneous necrosis: A case report. Issue 47 (25th November 2022) - Omameuda, Takahiko; Miyato, Hideyo; Sata, Naohiro; Lefor, Alan Kawarai
Abstract : Rationale: Methotrexate-associated lymphoproliferative disorder (MTX-LPD) is a major complication of methotrexate (MTX) therapy that can develop in patients with rheumatoid arthritis (RA), although primary hepatic MTX-LPD is extremely rare. Discontinuation of MTX results in remission in half of the patients with MTX-LPDs and is one treatment approach. Patient concern: A 64-year-old Japanese woman suffering from rheumatoid arthritis treated with MTX presented with upper abdominal pain. Diagnosis: Pathological evaluation showed that the tumor contained geographic necrosis and proliferation of large atypical lymphocytes strongly positive for cluster of differentiation 20 (CD20) antigen with immunohistochemical staining and Epstein-Barr Virus-encoded RNA transcript by in situ hybridization. The tumor was finally diagnosed as a primary hepatic MTX-associated Epstein-Barr Virus positive B-cell LPD. Interventions: Left hepatic lobectomy was performed for diagnosis and therapy. Outcomes: No sighs of recurrence were observed for 2 years. Lessons: This patient demonstrated that MTX-LPD could arise in the liver, although it is rare. If liver tumors arise in patients taking MTX, examination of sIL-2R, Epstein-Barr virus-VCA IgG and EBNA might support the diagnosis of MTX-LPD. In this case, the primary hepatic MTX-LPD became necrotic without discontinuation of MTX. It is generally believed that withdrawal of MTX restores antitumor immunity resulting in tumor necrosis. This case indicates that spontaneous regression might occur without any treatment in some patients treated for RA with MTX-LPD. The relationship between MTX-LPD and spontaneous necrosis is unclear and further data is required to characterize the types of patients that will develop spontaneous regression without intervention.